Short Communication: Genotyping of kdr allele in insecticide resistant-Aedes aegypti populations from West Sumatra, Indonesia - HASMIWATI HASMIWATI; SUPARGIYONO SUPARGIYONO (Biodiversitas Journal of Biological Diversity, 2018)
Hasmiwati, Supargiyono. 2018. Short Communication: Genotyping of kdr allele in insecticide resistant-Aedes aegypti populations from West Sumatra, Indonesia. Biodiversitas 19: 552-558. Aedes aegypti, the primary vector of Dengue fever, is widely distributed in Indonesia including in West Sumatra. Chemical insecticide is an effective way of shedding the chain of Dengue fever transmission. Long-term applications of insecticides have resulted in the development of resistance in Ae. aegypti populations. Knockdown resistance (kdr) allele as a result of point mutations has been found in Voltage-Gated Sodium Channel (VGSC) gene. This study aimed to design allele-specific primers to detect the kdr allele mutations. Ae aegypti samples were collected from several dengue endemic areas in West Sumatra. The susceptibility of adult mosquitos to insecticides was determined by bioassays using impregnation paper test with 0.18% malathion and 0.75% permethrin. In this study, we successfully confirmed that the A. populations have point mutations in the VGSC gene corresponding to S989P and V1016G amino acid substitutions. To genotype S989P and V1016G alleles, we designed kdr allele-specific primers based on the sequence of VGSC gene (NCBI Accession number No. EU399179.1. PCR analysis using the kdr allele-specific primers successfully identified the genotype of Ae. aegypti populations resistant to malathion and permethrin in West Sumatra.